Changes in cancer mortality in Shandong Province, China: a large population based study - Zhentao Fu; Fan Jiang; Zilong Lu; Jie Chu; Xiaohui Xu; Bingying Zhang; Xiaolei Guo; Aiqiang Xu; Jixiang Ma (Journal of the National Cancer Center)
ABSTRACT: Objective: To analyze the trend of major malignant tumor mortality in Shandong Province, eastern China from 1970 to 2021, and to provide the scientific basis for malignant tumor prevention and control. Methods: Cancer mortality data were sourced from three nationwide cause-of-death surveys and the Shandong Death Registration System. Trends in overall mortality and major causes of death were elucidated through indicators such as mortality rates and age-adjusted death rates, by comparing findings from the three comprehensive mortality surveys and the Shandong Death Registration System. The difference decomposing method was employed to estimate the contributions of non-demographic and demographic factors to the observed changes in cancer mortality. Results: From 1970 to 2021, the crude mortality rate of malignant tumors witnessed an overall increase in Shandong Province. The age-standardized mortality rate initially rose before subsequently declining. The proportion of cancer deaths among all causes of death increased initially and then stabilized at a high level of approximately 25 %. Both non-demographic and demographic factors played a role in the rise of the crude cancer mortality rate, with the proportion attributed to demographic factors gradually surpassing that of non-demographic factors. Despite the continuous increase in the crude mortality rate, the adjusted mortality rate exhibited a downward trend since 1990. Significant changes were observed in the ranking of the mortality rates of major cancers. For example, the mortality rate of lung cancer exhibited a continuous upward trajectory, ascending from the fifth to the first place and marking a 7.69-fold increase from 1970 to 2021. Conversely, digestive system tumors, including gastric cancer, esophageal cancer, and liver cancer, displayed varying degrees of decline, particularly in the standardized rates, which demonstrated a notable downward trend since 1990. The crude mortality rate of colorectal cancer and breast cancer showed an obvious upward trend, but the standardized rate did not rise significantly. For cervical cancer, both the crude and adjusted mortality rates displayed a pattern of initially decreasing and then increasing. Conclusions: Malignant tumors remain a significant threat to the residents of Shandong Province. The changing trends in various malignant tumors are inconsistent, underscoring the need for tailored intervention strategies to effectively control different types of malignant tumors.